Drug adherence and treatment duration for denosumab and mortality risk among hip fracture patients - Tsai, Yi-Lun; Wu, Chih-Hsing; Li, Chia-Chun; Shih, Chien-An; Chang, Yin-Fan; Hwang, Jawl-Shan; Tai, Ta-Wei (Osteoporosis international, 2023)
Summary This study aimed to assess the impact of drug adherence and treatment duration for denosumab on mortality risk after hip fracture surgery. Lower all-cause mortality risk was associated with drug intervals of 7 months or less and longer treatment duration. The study highlights the importance of proper denosumab administration. Purpose Prescription of anti-osteoporotic medications (AOMs) after osteoporotic hip fracture may increase bone mineral density (BMD) and decrease mortality risk. However, few studies have been conducted on drug adherence and treatment duration for denosumab, a popular choice among AOMs. This study aimed to assess the impact of denosumab adherence and treatment duration on the mortality risk of hip fracture patients after surgery. Methods We conducted a cohort study using nationwide population data from National Health Insurance Research Database (NHIRD) in Taiwan. Patients newly diagnosed with osteoporosis and hip fracture between 2008 and 2019 who used denosumab after surgery were included. We assessed drug adherence, treatment duration, and other parameters associated with patient outcomes. Results A total of 21,316 patients diagnosed with osteoporotic hip fractures were included. Compared with a > 7-month drug interval for denosumab, an interval of ≤ 7 months led to lower all-cause mortality risk (hazard ratio (HR): 0.60, 95% confidence interval (CI): 0.57 ~ 0.64). Patients with denosumab treatment for over 1, 2, and 3 years had lower all-cause mortality risk (HR&CI: 0.68 (0.64 ~ 0.73), 0.48 (0.43 ~ 0.53), 0.29 (0.26 ~ 0.33)) than those with treatment duration < 1 year. Analysis after excluding short-term death yielded similar results. Analysis of causes of death also showed that good adherence and longer duration were associated with reduced mortality due to cancer and cardiovascular disease. Conclusion Better drug adherence and longer duration of denosumab treatment are associated with lower all-cause mortality risk among hip fracture patients after surgery. Our study highlights the benefits of a proper time interval of denosumab administration. These findings provide important insight into management of osteoporotic hip fractures and may inform clinical practice and development of guidelines.